DIETARY SUPPLEMENTATION WITH BILLYGOAT-WEED (Ageratum conyzoides L.) LEAF MEAL: EFFECTS ON THE GROWTH PERFORMANCE AND SURVIVAL OF SNAKEHEAD FISH (Channa striata) - Nur Ikhlas Syuhada; Ronal Kurniawan; Rodhi Firmansyah; Windarti Windarti; Pebri Nanda Perdana; Okta Rizal Karsih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
Channa striata (snakehead fish) is a fishery commodity of high economic and medicinal value, yet a relatively slow growth rate constrains its culture. This study aimed to evaluate the effect of billygoat-weed (Ageratum conyzoides L.) leaf meal supplementation in feed on growth, feed efficiency, and survival of snakehead fish. The study used a one-factor Completely Randomized Design with four dose treatments (0, 5, 10, and 15 g/kg feed) and three replicates. Snakehead fingerlings measuring 6.00±1 cm were reared for 30 days and fed ad satiation. The results showed that the addition of billygoat-weed leaf meal affected absolute weight gain, specific growth rate, feed efficiency, and feed conversion ratio (p<0.05). The dose of 5 g/kg feed produced the best performance, with an absolute weight gain of 3.19±0.37 g, specific growth rate of 1.61±0.21%/day, feed efficiency of 161.85±14.99%, and FCR of 0.62±0.05, indicating that 5 g/kg feed is the optimal dose in snakehead fish feed and reflecting a hormetic response pattern at higher doses. The survival rate remained high across all treatments (93.33–98.33%), indicating the ingredient's safety up to the highest dose tested. In conclusion, billygoat-weed leaf meal has potential as a phytoadditive to enhance the growth performance of snakehead fish.